2012
DOI: 10.5402/2012/890280
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Yeast Endophytes from Poplar and Willow Promote Growth in Crop Plants and Grasses

Abstract: Endophytic associations with plants have a beneficial effect for many different plant species with some of them being host specific. Several endophytes isolated from poplar and willow were screened for their effects on commercially important crops including corn, tomato, pepper, squash, sunflower, and grasses. Most of these endophytes produce growth hormones such as indoleacetic acid (IAA) and have the nitrogenase gene required for nitrogen fixation. The effects of these isolates on plant growth and yield were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 34 publications
0
51
0
7
Order By: Relevance
“…Taghavi et al (2009) had reported a host-related specific response in endophytic bacteria inoculation studies on Populus hybrids and Khan et al (2012) had also reported similar host-related effects on other crop plants.…”
Section: The Inoculation Of the Endophytic Bacteria Alone (T3)mentioning
confidence: 99%
“…Taghavi et al (2009) had reported a host-related specific response in endophytic bacteria inoculation studies on Populus hybrids and Khan et al (2012) had also reported similar host-related effects on other crop plants.…”
Section: The Inoculation Of the Endophytic Bacteria Alone (T3)mentioning
confidence: 99%
“…Many of these organisms are considered tree symbionts or pathogens and were identified as being the origin of annotation of over 1,000 unique contigs (Figs. 7 and 8), including organisms such as T. uricae (spider mite; Grbi c et al, 2011), Melampsora laricipopulina (poplar leaf rust fungi; Rinaldi et al, 2007), Rhodotorula graminis (pigmented yeast; Khan et al, 2012), and Acanthamoeba castellanii (Herdler et al, 2008). The highly complex cross-talk indicated by such expression is best assessed through differential expression analysis because of the scale of information and uncertainty present within the system.…”
Section: Total Annotation Of the Global Transcriptome (Including Non-mentioning
confidence: 99%
“…Endophytic yeasts that have been found in plant leaves include both ascomycetous yeasts such as Candida guilliermondii, Candida oleophila, Candida railenensis, Cyberlindnera saturnus, Diutina siamensis, Metschnikowia pulcherrima, Wickerhamomyces anomalus and Wickerhamiella siamensis (Nassar et al, 2005;Isaeva et al, 2010;Rodríguez et al, 2011;Oliveira et al, 2012;Khunnamwong et al, 2014Khunnamwong et al, , 2015a (Gai et al, 2009;Abdel-Motaal et al, 2009;Isaeva et al, 2010;Khan et al, 2012;Akhtyamova & Sattarova, 2013;Khunnamwong et al, 2015b;Solis et al, 2015).…”
mentioning
confidence: 99%